Impact of climate change on production of selected agricultural commodities in Malaysia - Chizari, Ali (2017)
Climate change is arguably one of the most important factors influencing agricultural production in developing countries such as Malaysia. Malaysian population rely mostly on agriculture and other climate-dependent resources. However, inadequate attention has limited the country’s capacity towards adapting to climate change, while population increase continues to pose a serious challenge to food security. Therefore, it becomes important to explore the impacts of climate change on agricultural yield and production.